2020
DOI: 10.30935/cedtech/7993
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Video Modalities on Writing Achievement in Flipped English Classes

Abstract: This study investigated different modalities of videos in a flipped classroom for English writing classes in an intensive English program at a state university in Turkey. This quasi-experimental study was conducted with six experimental groups (n= 109) and one control group (n = 18). The dataset included the participants' scores of an essay pretest and two posttests, namely, recall and essay posttests. The data analysis showed that the experimental group viewing the video lecture which includes simultaneous pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 36 publications
(58 reference statements)
2
14
0
Order By: Relevance
“…When the former is applied, a significant increase in student achievement and performance can be seen. Hence, the findings of this study confirm the results stated by Akgün and Atıcı (2017), Ekmekçi (2014), İyitoğlu and Erişen (2017), Tutal and Yazar (2017), Umutlu (2016), Yavuz (2016. Bösner, Pickert and Stibane (2015), consider the increased success in the flipped classrooms a result of a cooperative environment and learning focused implementation.…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 91%
See 3 more Smart Citations
“…When the former is applied, a significant increase in student achievement and performance can be seen. Hence, the findings of this study confirm the results stated by Akgün and Atıcı (2017), Ekmekçi (2014), İyitoğlu and Erişen (2017), Tutal and Yazar (2017), Umutlu (2016), Yavuz (2016. Bösner, Pickert and Stibane (2015), consider the increased success in the flipped classrooms a result of a cooperative environment and learning focused implementation.…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 91%
“…As discussed in the literature review (Akgün & Atıcı, 2017;Umutlu, 2016;Yavuz, 2016) the flipped classroom model is more effective than traditional education in some studies. When the former is applied, a significant increase in student achievement and performance can be seen.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The four themes identified from the review of Table 1 and Table 2 ( (Adnan, 2017;Akgün & Atıcı, 2017;Alsancak-Sırakaya, 2015;Aşıksoy& Özdamlı, 2016;Aydın, B., 2016;Boyraz & Ocak, 2017;Çakır, 2017;Çalışkan, 2016;Çetin-Köroğlu & Çakır, 2017;Ekmekçi, 2017;Güç, 2017;Göğebakan-Atıcı & Yıldız, 2016;Göğebakan-Atıcı, Yıldız & Altınbaş, 2016;Karaca & Ocak, 2017;Kurt, 2017;Sağlam, 2016;Sarıgöz, 2017;Şahin, Cavlazoğlu & Zeytuncu, 2015;Şengel, 2016;Turan, 2015;Tugun, Uzunboylu & Özdamlı, 2017;Umutlu, 2016;Zengin, 2017). In others, authors reported an increase in the average scores, yet did not report a statistical analysis investigating the significance of the observed difference (Özpınar, Yenmez & Gökçe, 2016;Sezer, 2016).…”
Section: Results and Conclusionmentioning
confidence: 99%